In Situ Temperature Measurements at the Svalbard Continental Margin: Implications for Gas Hydrate Dynamics. (13th April 2018) - Riedel, M.; Wallmann, K.; Berndt, C.; Pape, T.; Freudenthal, T.; Bergenthal, M.; Bünz, S.; Bohrmann, G.
Abstract: During expedition MARIA S. MERIAN MSM57/2 to the Svalbard margin offshore Prins Karls Forland, the seafloor drill rig MARUM‐MeBo70 was used to assess the landward termination of the gas hydrate system in water depths between 340 and 446 m. The study region shows abundant seafloor gas vents, clustered at a water depth of ∼400 m. The sedimentary environment within the upper 100 m below seafloor (mbsf) is dominated by ice‐berg scours and glacial unconformities. Sediments cored included glacial diamictons and sheet‐sands interbedded with mud. Seismic data show a bottom simulating reflector terminating ∼30 km seaward in ∼760 m water depth before it reaches the theoretical limit of the gas hydrate stability zone (GHSZ) at the drilling transect. We present results of the first in situ temperature measurements conducted with MeBo70 down to 28 mbsf. The data yield temperature gradients between ∼38°C km −1 at the deepest site (446 m) and ∼41°C km −1 at a shallower drill site (390 m). These data constrain combined with in situ pore‐fluid data, sediment porosities, and thermal conductivities the dynamic evolution of the GHSZ during the past 70 years for which bottom water temperature records exist. Gas hydrate is not stable in the sediments at sites shallower than 390 m water depth at the time of acquisition (August 2016). Only at the drill site in 446 m water depth, favorable gas hydrate stability conditions are met (maximum vertical extent of ∼60 mbsf); however, coring did not encounter any gas hydrates. Key Points: First in situ temperature measurements with MeBo70 were conducted off Svalbard in water depths between 340 and 446 m Temperature gradients constrain gas hydrate dynamics during the past 70 years Favorable gas hydrate stability conditions are only met in water depths exceeding 446 m but no gas hydrate was recovered at any drill site